2012
DOI: 10.1080/01635581.2012.648300
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Green and White Tea Against Benzo(a)pyrene Induced Oxidative Stress and DNA Damage in Murine Model

Abstract: In the current investigation, the ameliorative effect of green tea (GT) and white tea (WT) against benzo(a)pyrene (BaP) induced oxidative stress and DNA damage has been studied in the livers and lungs of Balb/c mice. A single dose of BaP (125 mg/kg, b.w. orally) increased the levels of lipid peroxidation (LPO) and decreased endogenous antioxidants such as superoxide dismutase (SOD), glutahione reductase (GR), catalase (CAT), and glutathione (GSH) significantly. Pretreatment with GT and WT for 35 days before a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
5
29
0
1
Order By: Relevance
“…These reversible reactions generate superoxide anion radical and other reactive oxygen species (ROS) and can also directly react with nucleophilic sites on DNA. The metabolism of PAHs through peroxidative and AKR-mediated pathways is consistent with oxidative stress- associated PAH toxicity (Kumar et al ., 2012). …”
Section: Introductionmentioning
confidence: 68%
“…These reversible reactions generate superoxide anion radical and other reactive oxygen species (ROS) and can also directly react with nucleophilic sites on DNA. The metabolism of PAHs through peroxidative and AKR-mediated pathways is consistent with oxidative stress- associated PAH toxicity (Kumar et al ., 2012). …”
Section: Introductionmentioning
confidence: 68%
“…Several studies have shown the antioxidant effect of white (ALMAJANO; VILA; GINES, 2011;CALZUOLA;GIANFRANCESCHI;MARSILI, 2006;KOUTELIDAKIS et al, 2009;KUMAR et al, 2012;SEERAM et al, 2008;THRING;HILI;NAUGHTON, 2009) and green tea (KHAN et al, 2007;KUMAR et al, 2012;PANZA et al, 2008). Since obesity caused by high-fat diet is also associated to the increase in oxidative rather than reduction in hepatic production or uptake of endogenous lipids.…”
Section: Discussionmentioning
confidence: 99%
“…tea, white tea has been used to reduce oxidative stress and to treat obesity and associated diseases. However, most studies using white tea investigated its composition (ALCAZAR et al, 2007;MALINOWSKA et al, 2008;UNACHUKWU et al, 2010; VAN DER HOOFT et al, 2012), its antitumorigenic effect (ANGER; PETRE; CRANKSHAW, 2005;KUMAR et al, 2012;WANG et al, 2008), or its antioxidant action (ALMAJANO; VILA; GINES, 2011;CALZUOLA;GIANFRANCESCHI;MARSILI, 2006;KOUTELIDAKIS et al, 2009;LOPEZ;CALVO, 2011;PEREZ-JIMENEZ et al, 2011;SEERAM et al, 2008;THRING;HILI;NAUGHTON, 2009NAUGHTON, , 2011. Nonetheless, despite its popular use, there are no in vivo studies relating white tea and obesity associated with oxidative stress.…”
Section: Animals and Dietmentioning
confidence: 99%
“…It is a chemical carcinogen and teratogenic agent, and is produced spontaneously by environmental pollution such as traffic clustering and industrial production [11][12][13][14]. The carcinogenesis mechanism of [B(a)P] has been reported to involve DNA adduct formation during initiation stages.…”
Section: Introductionmentioning
confidence: 99%